Favorable effect of endoscopic reassessment of clinically staged T2 esophageal adenocarcinoma: a multicenter prospective cohort study - van de Ven, Steffi E. M.; Spaander, Manon C. W.; Pouw, Roos E.; Tang, Thjon J.; Houben, Martin H. M. G.; Schoon, Erik J.; de Jonge, Pieter J. F.; Bruno, Marco J.; Koch, Arjun D. (Endoscopy, 2021)
Background Clinical tumor stage of esophageal adenocarcinoma (EAC) is determined by endoscopic ultrasound and/or computed tomography scan, which have low accuracy for stages T1 and T2, potentially leading to overtreatment. We aimed to assess the proportion of cT2 EACs downstaged to cT1 after endoscopic reassessment (ERA) by an experienced interventional endoscopist.Methods We performed a prospective multicenter cohort study. Patients with cT2N0M0 EAC were included and underwent ERA. The primary outcome was proportion of cT2 EACs downstaged to cT1 after ERA.Results 15/25 included patients (60 %) were downstaged from cT2 to cT1 EAC after ERA and underwent attempted endoscopic resection. Endoscopic resection was aborted in 3/15 patients because of tumor invasion into the muscle layer; all three underwent successful surgical resection. Endoscopic resection was successful in 12/15 patients (80 %), all of whom had pT1 tumors. Overall, 10/25 (40 %) were treated with endoscopic resection alone.Conclusions ERA downstaged about half of the cT2 tumors to cT1, rendering them suitable for endoscopic resection. ERA had substantial clinical impact on therapeutic management, preventing overtreatment in 40 % of patients.